2016
DOI: 10.1021/acs.jpcb.5b12753
|View full text |Cite
|
Sign up to set email alerts
|

Femtosecond Heterodyne Transient Grating Studies of Nonradiative Deactivation of the S2 (11Bu+) State of Peridinin: Detection and Spectroscopic Assignment of an Intermediate in the Decay Pathway

Abstract: Femtosecond heterodyne transient grating spectroscopy was employed to investigate the nonradiative decay pathway from the S2 (1(1)Bu(+)) state to the S1 (2(1)Ag(-)) state of peridinin in methanol solution. Just as previously observed by this laboratory for β-carotene in benzonitrile, the real (absorption) and imaginary (dispersion) components of the transient grating signal obtained with Fourier transform spectral interferometry from peridinin exhibit ultrafast responses indicating that S2 state decays in 12 f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
66
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(70 citation statements)
references
References 86 publications
4
66
0
Order By: Relevance
“…The viscosity dependence reported here for the lifetime of the S x state, however, establishes for the first time that large-amplitude torsional motions promote nonradiative decay from S x to S 1 . As is also observed for the decay of excited states in triphenylmethane (TPM) dyes and in cyanines, the lifetime of the S x state follows a power law function with respect to the solvent viscosity (Figure a), which indicates that solvent friction retards progress along torsional coordinates toward a position-sensitive sink (or seam ,, ) leading to the S 1 state. But a better correlation of the lifetime of S x is obtained with respect to the average polar solvation time (Figure b), which suggests that the friction that slows the decay from S x to S 1 includes a solvent reorganization in response to the net transfer of charge that accompanies the twisting and pyramidalization of a CC bond. A comparable lifetime dependence was observed in the dye LDS–821, which exhibits a twisted intramolecular charge-transfer (TICT) excited state …”
supporting
confidence: 57%
See 1 more Smart Citation
“…The viscosity dependence reported here for the lifetime of the S x state, however, establishes for the first time that large-amplitude torsional motions promote nonradiative decay from S x to S 1 . As is also observed for the decay of excited states in triphenylmethane (TPM) dyes and in cyanines, the lifetime of the S x state follows a power law function with respect to the solvent viscosity (Figure a), which indicates that solvent friction retards progress along torsional coordinates toward a position-sensitive sink (or seam ,, ) leading to the S 1 state. But a better correlation of the lifetime of S x is obtained with respect to the average polar solvation time (Figure b), which suggests that the friction that slows the decay from S x to S 1 includes a solvent reorganization in response to the net transfer of charge that accompanies the twisting and pyramidalization of a CC bond. A comparable lifetime dependence was observed in the dye LDS–821, which exhibits a twisted intramolecular charge-transfer (TICT) excited state …”
supporting
confidence: 57%
“…Instead, as proposed previously, ,, the S x state is best assigned to a twisted form of the S 2 state. The time evolution of the high-frequency, CC bond stretching bands recently observed using transient IR and stimulated Raman spectroscopy by Di Donato et al supports the previous conclusion from pump–probe and pump–dump–probe spectroscopy by Zigmantas et al and Papagiannakis et al, respectively, that distortions of the conjugated polyene backbone of peridinin occur after optical preparation of the S 2 state.…”
mentioning
confidence: 97%
“…Nonetheless, this framework ignores the unique chemical nature of the peridinin Car-containing an allene tail and a lactone ring-that may support intramolecular-charge-transfer (ICT) character and even a separate ICT state [20]. Yet much like the claims of spectral evidence for dark intermediate states, the nature of ICT in peridinin remains controversially assigned, as evidenced by twenty-first-century experimental [21][22][23] and computational [24][25][26][27] investigations. On one hand, red-shifted emission with diminished lifetime in the face of polar solvent [20] and a distinct low-lying electronic excited state with ICT character [24] have been reported; on the other hand, conformational bright-state local minima [21,22] and bond-vibration-driven interplay between the lowest-lying bright-and dark-state properties [25] have been proposed as explanations for peridinin's anomalous photophysics.…”
Section: Introductionmentioning
confidence: 99%
“…Yet much like the claims of spectral evidence for dark intermediate states, the nature of ICT in peridinin remains controversially assigned, as evidenced by twenty-first-century experimental [21][22][23] and computational [24][25][26][27] investigations. On one hand, red-shifted emission with diminished lifetime in the face of polar solvent [20] and a distinct low-lying electronic excited state with ICT character [24] have been reported; on the other hand, conformational bright-state local minima [21,22] and bond-vibration-driven interplay between the lowest-lying bright-and dark-state properties [25] have been proposed as explanations for peridinin's anomalous photophysics. Whether ICT character exists as its own independent electronic excited state, and whether it impacts S 2 /S 1 state properties, may have important implications in energy transfer.…”
Section: Introductionmentioning
confidence: 99%
“…This picture seems to be also supported by the work of Ghosh et al, who identified a <20 fs nonradiative decay of the S 2 of peridinin to an S x state with a strong ICT character, assigned to a distorted configuration. 47 , 57 …”
mentioning
confidence: 99%